Examples of rural habitat models in the villages of Maadid : an archaeological study - Kouadria, Nadir (Journal of Social Sciences and Humanities, 2021)
In this research we studied rural habitat models in the region of Maadid which is administratively affiliated to the wilaya of Msila, where we dealt the following main problematic : What are the architectural characteristics of rural habitat in the region of Maadid ? In this way, we wanted to achieve a number of objectives , the most important of them was to document what was left of the rural habitat in some villages, and to highlight the architectural features of the rural habitat in the study area, by relying on three methodologies: historical, descriptive and analytical . Finally, we came to a main conclusion, that the design and formation of rural habitat in this region was influenced by environmental, social and economic factors.